Alpha beta but not gamma delta T cell clones in synovial fluids of patients with reactive arthritis show active transcription of tumour necrosis factor α and interferon γ. Issue 12 (16th November 2004) - Rihl, M; Gu, J; Baeten, D; Märker-Hermann, E; Goodall, J C; Gaston, J S H; Kuipers, J G; Zeidler, H; Yu, D T Y
Abstract : Objective: To compare the cytokine expression profile of three CD8+, three CD4+, and three γδ+ T cell clones all derived from the synovial fluids of three patients with reactive arthritis (ReA). Methods: Complementary DNA based microarrays containing the specific sequence of 56 cytokine transcripts were used for screening. Selected genes were confirmed by reverse transcriptase-polymerase chain reaction assay. Results: Microarray showed that transcripts encoding for interferon γ and tumour necrosis factor α were expressed by all CD8+ and CD4+ T cell clones. However, γδ+ T cells predominantly expressed transforming growth factor β2 and granulocyte monocyte-colony stimulating factor. Conclusion: T lymphocyte clones from the joint of patients with ReA exhibit differential cytokine expression profiles. CD8+ and CD4+ T cells demonstrate a Th1 mediated profile, whereas γδ+ T cells show a more heterogeneous and less proinflammatory Th3 driven pattern.